The Housing Market in Colombia: Socioeconomic and Financial Determinants - Sergio Clavijo; Michel Janna; Santiago Munoz (Inter-American Development Bank, Research Department, 2005)
This document provides an overview of the housing system in Colombia, exploring its socioeconomic and financial determinants and offering recommendations to improve the collection of basic data on the construction sector, household socioeconomic conditions, and mortgage markets. The paper also estimates a simultaneous econometric model for the country`s housing market using quarterly data over the period 1991-2004. On the demand side, we find that the area of approved licenses is highly elastic to households` disposable income, new housing prices and real interest rates on mortgage credit. On the supply side, we find high input-cost elasticity and a moderate response to wealth effects. These results prove to be robust to different proxies and diverse estimation procedures.
Keywords: 330; Wohnungsmarkt; Hypothek; Immobilienfinanzierung; Kolumbien